FINANCIAL INCLUSION TECHNOLOGY AND POVERTY REDUCTION IN NIGERIA (Journal of the Management Sciences, 2024)
This study investigates the impact of financial inclusion technologies—namely ATMs, POS systems, and mobile payments—on poverty alleviation in Nigeria. Using trend analysis and error correction econometric methods, the research evaluates how these technologies contribute to reducing poverty levels across different regions and demographics in the country. The findings reveal that ATMs and mobile payment systems significantly reduce poverty, primarily by enhancing access to financial services, promoting economic participation, and providing financial stability to low-income individuals. In contrast, POS systems do not exhibit a strong reductive effect on poverty, likely due to limited accessibility in rural areas and among the unbanked population. The study also highlights the positive role of financial deepening in poverty reduction, emphasizing the importance of expanding access to a wide range of financial services. The implications suggest that targeted investments in financial infrastructure, regulatory support, and financial literacy initiatives are essential to maximizing the poverty-alleviating potential of these technologies. The research concludes that a comprehensive approach to financial inclusion and deepening, tailored to the needs of underserved populations, is crucial for achieving sustainable poverty reduction and fostering inclusive economic growth in Nigeria.
Keywords: ATM, POS, Mobile Pay, Poverty.